Parking efficiency study for Kuantan Parade, Kuantan - Suriyana, Wagiman (2011)
Kuantan Parade is located in the middle of Kuantan town. This shopping complex area is one of the most compact business district in Kuantan. Shoppers to this malls come not only from this capital city of Pahang, but also from the neighbouring northern east coast states of Terengganu and KeJantan. This circumstances makes this area suffered from insufficient parking spaces that resulting in heavy traffic congestion especially during weekend. The objective of this research is to identify and locate the parking area that is available within the area. Basically based on the observation, we are going to determine the level usage of the parking area in term of demand versus supply. The results shown that, consumers prefer to park their vehicle near to the destination when the existing parking lots are not enough that leads to parking problems and traffic congestion. Action must be taken by the authority by providing more new parking spaces at strategic area.